Adaptive gamification in E‐learning: A literature review and future challenges - Bennani, Souha; Maalel, Ahmed; Ben Ghezala, Henda (Computer applications in engineering education, 2022)
The trend of gamification in online education has grown as technological advancements allow for more digitized learning environments to create interactive and engaging learning experiences. Learners are motivated in various ways, which necessitates an understanding of gamification mechanics and dynamics that produce enjoyment to adapt them to a variety of factors such as personality, needs, values, and motivations of each learner. Furthermore, exploration and advancement in the field of artificial intelligence (AI) allow us to provide an intelligent adaptive gamification environment. The aim of this study is to review the existing literature on adaptive gamification in e‐learning, as well as to highlight the scoops and future challenges of adaptive gamification applications. The present research followed the literature review method. For the data collected in this study, we used a qualitative approach. This paper presents in the first part a literature review of studies and a synthesis of the literature on the application of adaptive gamification in online education. The second part deals with the use of AI with adaptive gamification in online education and proposes its different techniques and future adaptation.